Characteristics of Petung Bamboo as the Main Structure of Wide Span Bamboo Hall Building at Gubukklakah, Poncokusumo, Malang - Busthomy, Maulana Aji Ali; Husna, Sofia Amalia; Bahar, Arsyad (Proceedings of the International Conference on Green Technology; Vol 10 (2019): Proceeding of International Conference on Green Technology, 2020)
Dendrocalamus asper, or commonly known as “petung bamboo”, is one of the local bamboo varieties that has a thick and wide stem perimeter. Based on its characteristics, petung bamboo has always been the ultimate choice to be utilized as the primary structure of bamboo buildings from a small span building until a wide span building. Nevertheless, there is limited access to the literature which studies the petung bamboo as the primary structure of wide span buildings. This problem had gained our attention to conduct examination and further study. The examination and analysis of petung bamboo as the primary structure in Gubukklakah Hall building is crucial, due to the structural material recommendation for the architectural design in the future. This study was focusing on the examination of petung bamboo’s characteristics as the primary structure of wide span buildings. There are several methods used in this study such as the qualitative method, literature studies, and case studies. Three important aspects will be discussed in the petung bamboo as the primary structure of the wide span building study framework: characteristics, strength, and on-site application. Hopefully, the study framework can give a positive contribution to Indonesian architecture development in terms of analytical data and documentation from petung bamboo as the primary structure in the Bamboo Hall Building.